Interactions between cover crops and soil microorganisms increase phosphorus availability in conservation agriculture - Hallama, Moritz; Pekrun, Carola; Pilz, Stefan; Jarosch, Klaus A.; Frąc, Magdalena; Uksa, Marie; Marhan, Sven; Kandeler, Ellen (Plant and soil, 2021)
Aims An essential task of agricultural systems is to improve internal phosphorus (P) recycling. Cover crops and tillage reduction can increase sustainability, but it is not known whether stimulation of the soil microbial community can increase the availability of soil organic P pools. Methods In a field experiment in southwest Germany, the effects of a winter cover crop mixture (vs. bare fallow) and no-till (vs. non-inversion tillage) on microbial P-cycling were assessed with soybean as the main crop. Microbial biomass, phospholipid fatty acids (PLFAs), P cycling enzymes, and carbon-substrate use capacity were linked for the first time with the lability of organic P pools measured by enzyme addition assays (using phosphodiesterase, non-phytase-phosphomonoesterase and fungal phytase). Results Microbial phosphorus, phosphatase, and fatty acids increased under cover crops, indicating an enhanced potential for organic P cycling. Enzyme-stable organic P shifted towards enzyme-labile organic P pools. Effects of no-till were weaker, and a synergy with cover crops was not evident. Conclusions In this experiment, cover crops were able to increase the microbially mediated internal P cycling in a non-P-limited, temperate agroecosystems.